Effect of the concentration, pH, and Ca2+ Ions on the rheological properties of concentrate proteins from quinoa, lentil, and black bean (2022)
ABSTRACT: Given consumer trends propelling a movement toward using plant protein in the food industry and searching for alternative protein ingredients by the industry, this study aimed to assess the influence of factors such as protein concentration, medium pH, and the presence of a divalent ion (Ca2+) upon the rheological properties such as viscosity change and gel formation of dispersion proteins extracted from quinoa, black beans, and lentils. A solution of each protein was prepared by varying its concentration (2.5%, 5.0%, and 10%), the pH (5.0, 7.0, and 9.0), and the incorporation of calcium chloride (0.0% and 1.0%). Each obtained solution was subjected to rheological tests to determine the parameters: consistency index (K), flow behavior (n), the storage (G’) and loss (G”) modules, and the phase shift angle (δ). The results demonstrate that the incorporation of Ca2+, the shift in protein levels, and the decrease in pH modified the rheological behaviors of proteins, which were also influenced by the structural characteristics of each protein studied. However, thermal treatment and protein concentrations caused the most significant impact on proteins’ rheological behavior, forming gels independently of other conditions. It was possible to study and interpret the studied proteins’ rheological variations according to the environment’s conditions.